The Powerlessness of Radical Consumption in Contemporary Performance: The Case of “Via Negativa” - Kunst, Bojana (Identities: Journal for Politics, Gender and Culture, 2011)
Author(s): Bojana Kunst Title (English): The Powerlessness of Radical Consumption in Contemporary Performance: The Case of “Via Negativa” Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 8, No. 1 (Winter 2011) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 115-127 Page Count: 12 Citation (English): Bojana Kunst, “The Powerlessness of Radical Consumption in Contemporary Performance: The Case of ‘Via Negativa,’” Identities: Journal for Politics, Gender and Culture, Vol. 8, No. 1 (Winter 2011): 115-127.